Is the Best Plate a Nail? A Review of 3230 Unstable Intertrochanteric Fractures of the Proximal Femur. Issue 2 (February 2018) - Tucker, Adam; Donnelly, Kevin J.; Rowan, Clare; McDonald, Sinead; Foster, Andrew P.
Abstract : Objectives: To evaluate the functional outcomes, revision, and mortality rates of 3 implants used for unstable intertrochanteric hip fractures; the sliding hip screw (SHS), with or without a trochanteric stabilization plate (TSP); and a cephalomedullary nail (CMN). Design: Multicentre National Prospective Cohort Study. Setting: Northern Ireland. Patient/Participants: Patients were identified from a prospective database. Fractures were classified according to OTA/AO A31A2.2, A2.3, and A3. All patients had a minimum of 12 months of follow-up. Intervention: Patients received either an SHS, an SHS in combination with a TSP, or a CMN. Implant choice was at the discretion of the operating surgeon. Outcome Measure: Primary outcome was 12-month mortality analyzed by the Kaplan–Meier survival analysis. Secondary outcomes included 12-month functional status using a validated score and all time revision of implants for any reason. Results: In total, 3230 patients met the inclusion criteria (2474 SHS, 158 SHS + TSP, and 598 CMN). CMN use increased over time, with concomitant reduction in SHS use. There was no significant difference in functional outcomes at 12 months (analysis of variance, P = 0.177). Although men were significantly younger, they were at a higher risk of 12-month mortality. CMNs had statistically significantly lower 12-month mortality rates ( P = 0.0148). The highest revision rate (4.04%) was seen in patients treated with SHS alone ( P = 0.041). Conclusions: The use of a CMN in unstable intertrochanteric hip fractures conveys the best results in functional outcomes, 12-month mortality, and has lower revision rates compared with an SHS ± TSP. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.